PERBANDINGAN UNSUR INTRINSIK KISAH NABI LUT ANTAR SURAT DALAM ALQURAN - Nur Aida (IAIN Kediri, 2021)
The prophet Lut was one of the prophets whom Allah told several times in al-Qur’an. In the same story, there are indications that Allah tells the story over and over again with a different intrinsic element. Findings about the similarities and differences in the intrinsic elements in the telling of the story of the Prophet Lut will be useful for the process of interpreting al-Qur’an specifically to understand the context of the Prophet Lut’s story.In addition, comparative research so far is in the form of intertextual studies, there has not been any research on the comparison of the intrinsic elements of the same story but it is repeated. So this paper will compare the intrinsic elements of the story of the Prophet Lut between letters in al-Quran. Using intrinsic element theory, namely identifying the plot, characterization, setting, point of view and theme of each letter that tells the storyof the Prophet Lut and then comparing them. With a qualitative approach from the source of al-Qur’an. The results show that differences occur in the plot, characterization, and setting. But the same is the theme and perspective. The differences occur not because the stories in al-Qur’an are contradictory, but because there are variations in the instrumental elements that serve to provide beauty, emphasis and psychological effects. For the interpretation of the verse of the story, in addition to understanding the meaning of the text, context, related science, and development science, it is also necessary to understand the intrinsic elements of the story because the differences in the presentation of the intrinsic elements are related to the intent of the message to be conveyed in the verse.Keywords: Comparison of Story, Intrinsic Elements, The Story of the Prophet Lut